2016
DOI: 10.1002/2016ja022969
|View full text |Cite
|
Sign up to set email alerts
|

Survey of whistler mode chorus intensity at Jupiter

Abstract: Whistler mode chorus emission is important in the acceleration of electrons and filling of the radiation belts at Jupiter. In this work chorus magnetic intensity levels (frequency‐integrated spectral density, PB) at Jupiter are comprehensively binned and parameterized. The frequency range of chorus under study extends from the lower hybrid frequency, flh, to fceq/2 and fceq/2 < f < 0.8 fceq, where fceq is the cyclotron frequency mapped to the magnetic equator. The goal is to obtain a quantized distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 38 publications
5
54
0
Order By: Relevance
“…An alternative acceleration process would have been energy diffusion from interaction with whistler waves (Woodfield et al, ). Since the intensity of these waves is small for L > 20 (Menietti et al, ), it is maybe not surprising that acceleration occurs through adiabatic transport instead.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative acceleration process would have been energy diffusion from interaction with whistler waves (Woodfield et al, ). Since the intensity of these waves is small for L > 20 (Menietti et al, ), it is maybe not surprising that acceleration occurs through adiabatic transport instead.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the present study provides direct evidence that diffuse auroral emissions at Jupiter are produced by electron precipitation covering a broad range of energy (0.1–700 keV) due to efficient pitch angle scattering. Although whistler mode waves have been suggested to cause pitch angle scattering into the loss cone (Bhattacharya et al, , ; Bolton et al, ; Mauk et al, ; Xiao et al, ), Galileo wave observations showed that these whistler mode emissions are commonly detected near the magnetic equator in the Jovian magnetosphere over 8–15 R J (Menietti et al, , ). Therefore, these whistler mode waves potentially responsible for causing diffuse auroral electron precipitations were not detected by Juno in the polar region during PJ1.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…However, in the diffuse auroral region, only weaker emissions were detected mostly below the proton cyclotron frequency. Whistler mode waves, which are suggested to cause pitch angle scattering of diffuse auroral electrons (Bhattacharya et al, , ; Bolton et al, ; Mauk et al, ; Xiao et al, ), are probably located near the magnetic equator in the Jupiter's middle magnetosphere (Bhattacharya et al, ; Menietti et al, ) and thus were not detected at this high latitude. It is interesting to note that weak electromagnetic emissions above the proton cyclotron frequency exhibited a sharp cutoff at M shell ~6, near the trajectory of Io.…”
Section: Juno Observation Of Auroral Emissions and Energetic Electronsmentioning
confidence: 99%
“…Readers are referred to the study of Xiao FL et al (2009) for details of the numerical scheme and method. Figure 1 shows the latitudinal dependence of B w over L J = 6-14 for upper band and lower band chorus, respectively, following the study of Menietti et al (2016). Clearly, in the Jovian radiation belts the typical wave amplitude is < 20 pT for lower band chorus (LBC) and < 2 pT for upper band chorus (UBC).…”
Section: (8)mentioning
confidence: 99%
“…A later study, Shprits et al () confirmed that interactions with whistler waves cause significant local acceleration of electrons at Jupiter, and indicated that the wave latitudinal distribution has a determining role in the dynamics of energetic electrons. Menietti et al () obtained a quantized distribution of chorus magnetic field intensity for use in stochastic modeling efforts, suggesting that chorus induced wave‐particle interactions at Jupiter may play an even greater role than earlier proposed. De Soria‐Santacruz et al () further clarified that the shape of the electron phase space density and the latitudinal extent of the chorus waves are important for both the acceleration and loss of Jovian radiation belt electrons.…”
Section: Introductionmentioning
confidence: 98%